Analysis of Misconceptions in FPB and KPK Material for Students - Purwaningtyas, Briyan Agustina; Sary, Ryky Mandar; Artharina, Filia Prima (International Journal of Elementary Education, 2020)
Students experience errors in the mastery of concepts, including incomplete writing solutions and students' inability to remember concepts. Students do not write the concepts used in solving FPB and KPK questions. This study aimed to analyze the types of misconceptions and causes of misconceptions in FPB and KPK material for grade IV students. This type of research is qualitative with a descriptive approach, with the research subject being fourth-grade elementary school students. Types of data collection used are written tests, interviews, and documentation. The analysis results regarding the misconceptions that occur in FPB and KPK material for fourth-grade elementary school students state that students experience translation misconceptions, sign misconceptions, arithmetic misconceptions, and systematic concept misconceptions, and operation misconceptions. The causes of misconceptions are due to factors from students related to interest in learning because they already think that mathematics is a complicated subject, factors from teachers who do not provide in-depth explanations related to FPB and KPK material, conditions or situations in the classroom that cause the subject to be unable to concentrate and pay attention to the teacher when giving explanations about FPB and KPK material, students' understanding of the FPB and KPK material is still low and wrong preconceptions. Based on the research results, it can be concluded that the types of misconceptions that occur in grade IV students are translation misconceptions, sign misconceptions, arithmetic misconceptions, systematic misconceptions, concept misconceptions, and operation misconceptions.